Immunoblot technique to visualise serum pepsinogen A isozymogen patterns. - Zwiers, A (1990)
Pepsinogen A (PGA) isozymogen patterns in urine and gastric mucosa can be visualised in non-denatured polyacrylamide gel electrophoresis by showing proteolytic activity after the conversion of pepsinogen into pepsin by acid. This method is not suitable for visualising PGA patterns in serum due to low PGA concentrations. To obtain a more sensitive visualisation method an immunoblotting technique was developed. PGA isozymogen patterns from urine and sonified gastric mucosa specimens obtained by immunoblotting were identical with those obtained by activity staining. The immunostaining method was at least 50 times more sensitive. PGA isozymogen patterns could be visualised in serum. Preliminary results suggest that the PGA patterns in serum and gastric mucosa are identical. As an association has been found between the genetically determined PGA isozymogen patterns in gastric mucosa and gastric malignancies in man, immunoblotting of PGA isozymogens in serum may provide a screening tool for subjects at risk of malignant gastric disease.